2014
DOI: 10.1186/1749-7221-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of conventional and new electrophysiological techniques in carpal tunnel syndrome and their relationship to body mass index

Abstract: The purpose of this study is to evaluate prospectively the sensitivities of conventional and new electrophysiological techniques and to investigate their relationship with the body mass index (BMI) in a population of patients suspected of having carpal tunnel syndrome (CTS).In this study, 165 hands of 92 consecutive patients (81 female, 11 male) with clinical diagnosis of CTS were compared to reference population of 60 hands of 30 healthy subjects (26 female and 4 male). Extensive sensory and motor nerve condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Majority of the subject group were females (85.6%) but no significant difference was identified when the relationship of CTS severity and gender was investigated. Compatible with the distribution of our subjects, generally in the studies 12 , 13) CTS is seen more frequently in the female gender. In some studies it has been reported that the female gender is an independent risk factor.…”
Section: Discussionsupporting
confidence: 71%
“…Majority of the subject group were females (85.6%) but no significant difference was identified when the relationship of CTS severity and gender was investigated. Compatible with the distribution of our subjects, generally in the studies 12 , 13) CTS is seen more frequently in the female gender. In some studies it has been reported that the female gender is an independent risk factor.…”
Section: Discussionsupporting
confidence: 71%
“…Carpal tunnel syndrome is the most common entrapment neuropathy, with a 10% lifetime risk in the general population (American Academy of Neurology, 1993aNeurology, , 1993bAygul et al, 2009;Duncan et al, 1987;Jablecki et al, 1993;Katz et al, 1998;Padua et al, 1997;Spitzer, 1996;Wilson and Sumner, 1995;You et al, 1999). Carpal tunnel syndrome results from compression of the median nerve during passage through the carpal tunnel under the transverse carpal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…The classification is based on the clinical observations and scientific investigations that nerve entrapment of CTS affects earlier sensory nerve than motor nerve (American Academy of Neurology, 1993aNeurology, , 1993bAygul et al, 2009;Heybeli et al, 2002;Jablecki et al, 1993;Katz et al, 1998;Levine et al, 1993;Padua et al, 1997;Spitzer, 1996;You et al, 1999). Mild CTS is indicated when the patient complains of the typical symptoms of CTS and shows Tinel sign or positive Phalene maneuver (inclusion of the aforementioned American Academy of Neurology practice parameters criteria 1 and 4), but the sensory and motor function tests of the affected hand are normal (exclusion of criteria 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus (DM), thyroid disease, connective tissue disease, amyloidosis, acromegaly, and pregnancy are other risk factors that can influence CTS development [5]. CTS is more prevalent in women than men [6,7] and female gender is reported as an independent risk factor [5]. Its incidence has been reported as 136 and 506 per 100,000 people in men and women, respectively [8].…”
Section: Introductionmentioning
confidence: 99%